Carbon dots production via pyrolysis of sago waste as potential probe for metal ions sensing - Tan, Xian Wen; Ain Nadirah, Romainor; Chin, Suk Fun; Ng, Sing Muk (Elsevier B.V., 2013)
This work reports the synthesis of carbon dots (C-dots)from sago industrial waste using thermal pyrolysis approach. The pyrolysis condition was found to govern the carbonisation conversion of bulk sago waste into carbon rich residue that can be further isolated to obtain carbon dots. In order to obtain the best yield ofthe carbon dots, optimization ofthe thermal pyrolysis conditions have been performed which consisted of varying temperature of carbonisation at a constant heating duration. The C-dots can be dispersed in aqueous media and portrayed a significant fluorescent property that can be observed by naked eye under a UV light source. The optimum temperature of carbonisation was determined at 400 ◦C in which the strongest fluorescence emission was record at 390 nm with the optimum excitation wavelength of 315 nm. The fluorescence of the C-dots was found to be significantly quenched in the presence of various metal ions. Thus, the C-dots can be adopted as a potential optical probe for sensing of metal ions in aqueous media. An analytical characterization has been performed in this study over a series of commonly available metal ions and the sensing characteristics were evaluated using the standard Stern–Volmer quenching model. This study has successfully demonstrated an innovative approach of converting agricultural waste into high value optical sensing receptors for metal ions detection.